Spectrophotometric method for hg(ii) determination in aqueous environment using zinc-dithizonate complex - Musa Ahmad Ahmad,; Elya Sufliza Marsom; Harun Hamzah (Universitas Gadjah Mada, 2001)
This article described the use of zinc-dithizonate for spectrophotometric determination of Hg(II) in aqueous environment. Zinc dithizonate was found to react selectively with Hg(II) to give a reddish yellow complex with optimum absorbance at pH 1.0. This complex was found to be useful for spectrophotometric determination of aqueous Hg(II) in the concentration range of 1.0 - 12.0 ppm. This method was also found to be reproducible with calculated relative standard deviation, RSD of 1.08%. At 1:1 mole ratio, interfering ions such as CH COO·, Pb2+ and Ag+ were found to interfere at degree 3 of interference of more than 10.0%.